A Review on Computer Aided Drug Design – In Silico - Pranali R. Bhujade; Khemutai G. Shedame; Pooja R. Hatwar; Dr. Ravindra L. Bakal; Krushnali N. Nehar; Ankita Y.Gawai (Asian Journal of Pharmaceutical Research and Development, 2024)
The process of drug discovery takes a long time and costs a lot of money. Computer-Aided Drug Design (CADD) has become an important part of modern drug discovery because it speeds up the process and lowers prices. CADD includes many methods, such as Structure-Based Drug Design (SBDD) and Ligand-Based Drug Design (LBDD). These use computer programs to do things like molecular docking, virtual screening, QSAR, pharmacophore modeling, and molecular dynamics. LBDD is used when the shapes of receptors are unknown, while SBDD uses machine learning. This review provides a comprehensive overview of CADD methods, classification, principles, and uses in drug creation. The article discusses about how important it is to find targets, find lead compounds, and make things work better. It also talks about the role of computers in pharmaceutical chemistry and molecular biology. CADD has increased the speed and accuracy of drug finding, making it possible to find new medicines. The review shows how CADD could change the way drugs are made, help people who don't have access to proper medical care, and make patient results better. Researchers can speed up the process of finding new drugs by using CADD strategies. This review is a great resource for researchers, clinicians, and industry workers who want to use CADD in pharmaceutical research. Using CADD has changed the way drugs are found, and its continued growth could lead to better health for everyone.